2019
DOI: 10.1016/j.psychres.2019.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of schizophrenia outpatients in residential care facilities with those living with someone: Study of mental and physical health, cognitive functioning, and biomarkers of aging

Abstract: This paper aims to compare mental and physical health, cognitive functioning, and selected biomarkers of aging reflecting metabolic pathology and inflammation, in outpatients with schizophrenia from two residential settings: residential care facilities (RCFs) and living with someone in a house/apartment. This cross-sectional study examined community-dwelling adults with schizophrenia either in RCFs (N = 100) or in a house/apartment with someone (N = 76), recruited for two NIH-funded studies in San Diego. Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
3
8
0
Order By: Relevance
“…Furthermore, a higher proportion of people living in rental accommodation were smokers, consistent with the literature that smoking is more prevalent in the socioeconomic disadvantaged [70] and people with lower income [71]. Lee et al (2019) showed that residents with schizophrenia in homes smoked more cigarettes, suggesting living arrangements may influence smoking behavior [72].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, a higher proportion of people living in rental accommodation were smokers, consistent with the literature that smoking is more prevalent in the socioeconomic disadvantaged [70] and people with lower income [71]. Lee et al (2019) showed that residents with schizophrenia in homes smoked more cigarettes, suggesting living arrangements may influence smoking behavior [72].…”
Section: Discussionsupporting
confidence: 85%
“…For example, individuals with schizophrenia or bipolar disorder may be more susceptible to COVID-19 infection 4 , 5 and, if infected, those with schizophrenia appear to be more than three times as likely than persons without schizophrenia to experience a severe clinical course 6 . Reasons for these disparities are many and varied but likely include greater vulnerability to stress 7 , 8 , reduced access to healthcare services 9 , 10 , increased prevalence of high risk factors such as obesity or diabetes 11 , 12 , and/or greater likelihood of communal living situations 13 where rates of transmission could be increased.…”
Section: Introductionmentioning
confidence: 99%
“…However, in residential care facilities, healthcare workers continue to assist severe patients during the process of activities of daily living. This assistance may decrease the capacity-performance discrepancy and improve mental and physical health [ 38 ]. Nevertheless, this cross-sectional study did not determine a causal relationship between the capacity-performance discrepancy and environmental barriers.…”
Section: Discussionmentioning
confidence: 99%